A Case Study On Malaysian Unit Trusts: Investors' Confidence And Performance - Lin, Goh Boon (2002)
The whole objective of this study is to quell any misconception potential investors may have concerning unit trust investment. Past research have revealed that the literacy level of investors in unit trust require improvement. This study elaborates and focuses on four areas to strengthen and dismiss negative elements associated to unit trust. The areas are; the regulatory system governing unit trust industry, the fund fees, funds performances and the competency level of distributors.